Análisis socioeconómico de los mendigos adultos mayores en la ciudad de Quito, provincia de Pichincha, en la localidad del centro histórico de quito en el periodo enero – julio 2015, y la intervención de la trabajadora social. - Espinosa Vaca, Marcela Ibeth (2018)
Social work in its various expressions runs to the multiple and complex relationships between individuals and the environment in which they operate. Its mission, enabling all people to display their potential, ennoble their lives and preventing many changes in bodily functions. The issue around which rotates the present research refers to the "Socioeconomic analysis of the elderly beggars in the city of Quito, Pichincha province, in the town of Old Quito in the period January to July 2015, and the intervention of the social Worker "which addresses issues of educational, cultural and social level where social work professionals should take to guide and optimize the quality of life of the elderly beggars. Professional social work is focused on problem solving and change, being important for the families of beggars find a course that will allow them to have alternatives to begging and thus improve their quality of life. Therefore, as professionals in this field must seek change in society and in the lives of individuals, families and communities they work With the implementation of the proposed project techniques such as observation and survey interesting results contributed to the development of the alternative proposal they were determined. Determined that most beggars are aged between 71 and 80 years of age, of whom the majority are men and with little educational background and marital status is married or widowed. It was also determined that begging is carried out with your partner or a family member for more financial resources in view that no state aid as Bonus human development. In addition to having direct contact with beggars it determined that their precarious economic situation leads them to this activity, which carried for years and may raise up to $ 3 a day with which they have to survive and contribute to the home, which creates problems additional health such as poor diet and constant abuse they receive. Also this research, aims to become an area of reference for people who you are framed in this social problem that exists nationally and even internationally.